1996
DOI: 10.1074/jbc.271.16.9347
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved HPD Sequence of the J-domain Is Necessary for YDJ1 Stimulation of Hsp70 ATPase Activity at a Site Distinct from Substrate Binding

Abstract: The 46-kDa protein YDJ1 is one of several known yeast homologues of the Escherichia coli DnaJ protein. Like all J homologues, it shares homology with the highly conserved NH2-terminal "J-domain" of DnaJ. A component of the DnaK (Hsp70) chaperone machinery that mediates protein folding, DnaJ is necessary for survival at elevated temperatures. It stimulates ATP hydrolysis by DnaK and effects the release of DnaK-bound polypeptides. Previous genetic and biochemical studies indicate that the J-domain is necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
229
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(246 citation statements)
references
References 62 publications
9
229
0
2
Order By: Relevance
“…This is consistent with our previous observation that auxilin still binds to clathrin baskets after its J-domain is removed, suggesting that auxilin has separate clathrin-binding and Hsc70-binding domains (12). However, the auxilin J-peptides containing the HDPK region do not show the same nucleotide dependence as auxilin in their interaction with Hsc70; in contrast to a similar peptide from the J-domain of YDJ1 (28), they appear to interact with Hsc70 like any other peptide substrate. Therefore, more work is required to determine exactly which portions of the J-domain are crucial to its proper interaction with Hsc70.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with our previous observation that auxilin still binds to clathrin baskets after its J-domain is removed, suggesting that auxilin has separate clathrin-binding and Hsc70-binding domains (12). However, the auxilin J-peptides containing the HDPK region do not show the same nucleotide dependence as auxilin in their interaction with Hsc70; in contrast to a similar peptide from the J-domain of YDJ1 (28), they appear to interact with Hsc70 like any other peptide substrate. Therefore, more work is required to determine exactly which portions of the J-domain are crucial to its proper interaction with Hsc70.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, we synthesized the two similar length peptides (auxilin J-peptides) shown in Fig. 6, analogous to the peptides prepared from YDJ1 by Tsai and Douglas (28). We found that both J-peptides caused about a 3-fold activation of the Hsc70 ATPase activity, but in contrast to auxilin, both peptides bound very weakly in ATP.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Modulation of activation-induced cell death J Syken et al dnaJ and Hsp70 family proteins (Wall et al, 1994;Tsai and Douglas, 1996). The H121Q TidS protein will efficiently interact with TidS-specific substrates but because of its lack of Hsp70 interaction cannot function as a chaperone and acts as a dominant-negative mutant (Syken et al, 1999).…”
Section: Modulation Of Activation-induced Cell Death J Syken Et Almentioning
confidence: 99%
“…A modest inhibition of growth is observed in U373 following infection with control virus, indicating a cytotoxic effect of the virus on the cells. DnaJ protein function is dependent upon a highly conserved histidine-proline-aspartate (HPD) sequence located within the J-domain [29]. Mutation of one or all of the amino acids completely abolishes J-domain-mediated stimulation of Hsp70 ATPase activity.…”
Section: Htid-1 L and Htid-1 S Have Differential Effects On Cell Viabmentioning
confidence: 99%